Evaluation of antiinflammatory, antioxidant and antiproliferative activities of Quassia borneensis Noot. (Simaroubaceae) extracts - Firdaus Kamarulzaman,; Julenah Ag Nuddin,; Kai, Li Lim; Aishah Adam,; Ahmad Sazali Hamzah,; Ahmad Rohi Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Quassia borneensis has been traditionally used as antihypertensive agent without any scientific literature on its mechanism of action. The objective of this study was to evaluate the antiinflammatory, antioxidant and antiproliferation properties of Q. borneensis extracts. The hexane, chloroform and aqueous extracts of root and bark of Q. borneensis were subjected to nitric oxide (NO) inhibition assay in LPS-stimulated RAW 264.7 cells. Expression of inducible NO synthase (iNOS) protein level was analyzed by Western blot. The antioxidant and antiproliferative activities of the extracts on HL-60 cells were determined using Ferric Reducing Antioxidant Power (FRAP) and MTT assays, respectively. The chloroform extract of Q. borneensis root obtained by soxhlet method (CSR) significantly inhibited 97.64 ± 0.96% of NO production (p < 0.001) and suppressed iNOS expression (p < 0.05) at the highest concentration of 1.0 μg/ml. The chloroform extract of bark obtained by maceration (CMB) exhibited the highest antioxidant capacity in the absence and presence of HL-60 cells, where the FRAP value were 125.45 ± 9.10 μM FeSO4.7H2O and 181.55 ± 3.45 μM FeSO4.7H2O, respectively. The greatest inhibition of HL-60 cell proliferation was exhibited by the chloroform extract of bark obtained by soxhlet method (CSB) with the IC50 of 5.0 μg/ml. The findings suggested that the chloroform extracts of Q. borneensis possess antiinflammatory, antioxidant and antiproliferative activities.